An integrative group intervention for the enhancement of emotional intelligence, empathy, resilience and stress management among police officers. (3rd September 2019) - Romosiou, Vasiliki; Brouzos, Andreas; Vassilopoulos, Stephanos P.
ABSTRACT: This study investigates the effectiveness of an integrative group program of four 4-h sessions, designed to enhance emotional intelligence, empathy, resilience and stress management skills among police officers. Fifty police officers participated in this study, allocated to either the intervention group ( n  = 23) or the control group ( n  = 27). The participants completed various self-report questionnaires both before and after the implementation of the program, as well as three months later. Results indicated significant improvement of emotional intelligence, empathy, resilience and stress management levels in the intervention group, compared to the control group. In addition, the positive changes remained significant three months after the termination of intervention. This study provides empirical evidence supporting the effectiveness of an intensive, broad targeting group program, which could be integrated into the Police Academies to bring benefits at an individual, social and organizational level.